The Role of Parents in Shaping the Foundation of Responsible Behaviour through Environmental Education - Suras, Febriana Ekananda; Auriza, Maghfirota; Cholimah, Nur (Universitas Negeri Makassar, 2024)
This study aims to describe the results of the analysis of how the role of parents in supporting the formation of children's responsibility for the environment and the analysis of the results of children's ability to be responsible for the environment. This research uses a qualitative research approach with this type of research is descriptive to find information on a topic related to the role of parents and the ability of responsibility in children. The data collection methods used in this study are interviews and documentation. The subjects used in this study are 3 parents who have children aged 4-6 years. The findings will describe the results qualitatively through several stages, namely data analysis and interpretation of results. The results of the study show that the role of parents in shaping responsible behavior towards the environment using the methods of discussion, habituation, and advice, and the ability of children's responsibility for the environment still needs to be developed. So that the role of parents still needs to be developed and continued so that children's development is formed optimally.